ANALISIS FAKTOR GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN KONFLIK TERHADAP TURNOVER KARYAWAN BAGIAN SEWING PT. SOLO KAWISTARA GARMINDO - Tiyas Dwi Dwi Hapsari; Istiqomah Istiqomah; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2020)
This research goals to know and explain the effectaccording to the simultaneous and partial method inLeadership Style(X1), Fieldwork(X2),, and Conflict(X3) Towards Turnover Employees in Sewing Section in PT. Solo KawistaraGarmindo. The population in this research is 300 respondents taken from the permanent employees in sewing section. The samples of this research are 75 employees. Sampling technique uses the nonprobability sampling method. The kind of this research is a descriptive quantitative research. The method of collecting data is using questionnaires. The technique of data analysis uses multiple linear regressions. The result of the research shows that F-test of leadership style, fieldwork, and conflict simultaneously and significantly affect the turnover. The result of T-test shows that the leadership style partially does not affect toward the turnover, on the other hand, fieldwork and conflict partially affect toward the turnover. The model of multiple linear regressions in this research is Y = 10, 972 – 0,392 X1 + 0,286 X2 + 0,759 X3. Tended to thenext researchers, they should add another variables that can affect the level of turnover employees, because by the decline in turnover rates, it will affect the company, because the leadership style variables that examined in this research indicate no influence, so it is expected for the company leaders in PT. KawistaraGarmindo to improve the self-quality of the current leadership and expected in the future, to bemore improved in the effort in improving the performance so that it can be more productive and reduces the turnover employees. Keywords : Leadership Style, Fieldwork, Conflict, Turnover